1977
DOI: 10.1128/aac.11.3.475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2-Deoxy- d -Glucose and 3-Deazauridine Individually and in Combination on the Replication of Japanese B Encephalitis Virus

Abstract: We have tested the potencies of the competitors of glucose, 2-deoxy-i>.glucose, and of uridine, 3-deazauridine, on the inhibition of Japanese B encephalitis virus multiplication in BHK-21 cell cultures. The relative effectiveness of the viral inhibitors were evaluated individually and in combination in relation to cytotoxicity as a measure of the selectivity of inhibition. When the drugs were administered individually, the antiviral activity was masked by the cytotoxic effect on the host. By combining the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Previous publications have identified that treatment of cells with 2-DG reduces the replication of a variety of viruses, including CVB3 (77)(78)(79)(80)(81)(82)(83). Limiting the energy supplies in an infected cell would affect protein synthesis and the assembly of viral progeny.…”
Section: In Tsc2mentioning
confidence: 99%
“…Previous publications have identified that treatment of cells with 2-DG reduces the replication of a variety of viruses, including CVB3 (77)(78)(79)(80)(81)(82)(83). Limiting the energy supplies in an infected cell would affect protein synthesis and the assembly of viral progeny.…”
Section: In Tsc2mentioning
confidence: 99%
“…Our study, to the best of our knowledge, is the first to demonstrate the antiretroviral activity of formycin A. Many previous studies identified the activity of 3-deazauridine against riboviruses (20)(21)(22)(23)(24)(25)(26) and retroviruses (23,27). Interestingly, 3-deazauridine was previously observed to potentiate the anti-HIV-1 activity of 3TC and dideoxycytosine (28).…”
Section: Discussionmentioning
confidence: 86%
“…This study reported that 2-DG intervenes in the synthesis and elongation of oligosaccharides in the viral envelope glycoproteins. Based on this pioneering study, many experimental studies pertaining to inhibition of viral infection by 2-DG was explored subsequently, which included viruses belonging to the family of Paramyxoviridae, Rhabdoviridae, Togaviridae (Kaluza et al, 1972) [10] , Herepesviridae (Courtney et al, 1973) [4] , Flaviviridae (Woodman et al, 1977) [23] , Adenoviridae (Xi et al 2014) [26] and Retroviridae (Blough et al, 1986) [2] .…”
Section: Historymentioning
confidence: 99%
“…Experimentation of 2-DG in viral replication has been reported since the late 1950s, with the first report on the significant reduction of influenza virus concentration in the chorio-allantoic membrane of embryonated chicken egg (Kilbourne, 1959) [12] . Ever since then, 2-DG has been explored as an anti-viral agent in Herpesviridae (Courtney et al, 1973;Radsak et al, 1981) [4,17] , Flaviviridae (Woodman et al, 1977) [23] , Orthomyxoviridae (Kaluza et al, 1972;Kilbourne, 1959) [10,12] , Rhabdoviridae (Kaluza et al, 1972) [10] , Retroviridae, Paramyxoviridae (Tripathy and Mohanty, 1979) [21] , Togaviridae (Kaluza et al, 1972) [10] and Picornaviridae. The details of previous studies detailing the effect of 2-DG on various viruses have been tabulated (Table 1).…”
Section: -Dg In Viral Replicationmentioning
confidence: 99%